Theory of scattering : papers in honor of Henry Eyring - Eyring, Henry, 1901-1981; Henderson, Douglas, 1934- (Theoretical chemistry, 1981)
Theoretical Chemistry: Theory of Scattering: Papers in Honor of Henry Eyring, Volume 6, Part A covers the aspects of reactive and nonreactive scattering. The book discusses the applications of classical trajectory to reactive scattering and the accurate quantum calculations of reactive systems. The text also describes the fluctuations in chemically reacting systems, as well as the coupling of electronically adiabatic states in atomic and molecular collisions. Chemists, physicists, people involved in the study of the theory of scattering, and students taking related courses will find the book u.